A pH-responsive liposomal nanoplatform for co-delivery of a Pt(IV) prodrug and cinnamaldehyde for effective tumor therapy - Tang, Ting; Gong, Yufang; Gao, Yuan; Pang, Xinlong; Liu, Shuangqing; Xia, Yulan; Liu, Dongsheng; Zhu, Lin; Fan, Qing; Sun, Xiao (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The tumor microenvironment (TME) is mainly characterized by abnormally elevated intracellular redox levels and excessive oxidative stress. However, the balance of the TME is also very fragile and susceptible to be disturbed by external factors. Therefore, several researchers are now focusing on intervening in redox processes as a therapeutic strategy to treat tumors. Here, we have developed a liposomal drug delivery platform that can load a Pt(IV) prodrug (DSCP) and cinnamaldehyde (CA) into a pH-responsive liposome to enrich more drugs in the tumor region for better therapeutic efficacy through enhanced permeability and retention effect. Methods: Using the glutathione-depleting properties of DSCP together with the ROS-generating properties of cisplatin and CA, we synergistically altered ROS levels in the tumor microenvironment to damage tumor cells and achieve anti-tumor effects in vitro. Results: A liposome loaded with DSCP and CA was successfully established, and this liposome effectively increased the level of ROS in the tumor microenvironment and achieved effective killing of tumor cells in vitro. Conclusion: In this study, novel liposomal nanodrugs loaded with DSCP and CA provided a synergistic strategy between conventional chemotherapy and disruption of TME redox homeostasis, leading to a significant increase in antitumor effects in vitro.